72-h kinetics of high-sensitive Troponin T and inflammatory markers after marathon - Scherr, J.; Braun, S.; Schuster, T.; Hartmann, C.; Moehlenkamp, S.; Wolfarth, B.; Pressler, A.; Halle, M. (Medicine & Science in Sports & Exercise, 2011)
Introduction: Strenuous exercise induces significant increases in cardiac biomarkers. However, it is still unclear whether this is caused by cardiomyocyte necrosis or secondary mechanisms such as ischemia, cardiac energy deficiency, increased inflammation, or renal dysfunction.